Prevalence of aspiration Pneumonia in Stroke Patients at Tertiary Care Hospital - Muhammad Khalid, Iftikhar Ali Kakar, Haris Khan, Muhammad Haroon Shahid, Hazrat Abbas, Muhammad Salman, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: One of the major health problems after stroke is aspiration pneumonia which might cause death. Aspiration pneumonia occurs in patients both with ischemic stroke and hemorrhagic stroke. Objective: To assess the prevalence of aspiration Pneumonia in stroke patients Methodology: This descriptive and cross-sectional study was carried out at the Medicine department, Qazi Hussain Ahmad Medical Complex, Nowshera from July 2020 to July 2021. By using pre-designed Performa, all the data including stroke type, name, age and gender of the patient and diagnosis of aspiration pneumonia were documented. All the analysis of the recorded data was carried out by employing SPSS version 24. Results: In the current study, totally 180 patients were enrolled. There were 102 (56.67%) males participants while female participants were 78 (43.33%). On the basis of age distribution, 69 (38.335%) patients were observed in age group 40-60 years whereas 111 (61.67%) patients were observed in age group 61-80 years. The mean age (SD) in the current study was 61 (3.11) years. Based on type of stroke, 117 (65%) patients were observed with ischemic stroke whereas 63 (35%) patients were observed with hemorrhagic stroke. The overall frequency of aspiration pneumonia in stroke patients was 15.56% (n=28). Practical implication: Our study will provide physicians with new data that early diagnosis for aspiration pneumonia in stroke patients should be done to reduce the morbidity and mortality rates. Conclusion: Aspiration pneumonia is highly prevalent in stroke patients in our setting. Our study recommends that early diagnosis for aspiration pneumonia in stroke patients should be done to reduce the morbidity and mortality rates. Keywords: Prevalence; aspiration Pneumonia; stroke; diagnosis; morbidity; mortality